P-glycoprotein expression and localization in the rat uterus throughout gestation and labor. Issue 3 (September 2016) - Huang, Qi-Tao; Shynlova, Oksana; Kibschull, Mark; Zhong, Mei; Yu, Yan-Hong; Matthews, Stephen G; Lye, Stephen J
Abstract : Uterine tissues contain the efflux transporter P-glycoprotein (P-gp, encoded by Abcb1a/1b gene), but little is known about how it changes through gestation. Our aim was to investigate the expression profile and cellular localization of P-gp in the pregnant, laboring and post-partum (PP) rat uterus. We propose that during pregnancy the mechanical and hormonal stimuli play a role in regulating myometrial Abcb1a/1b/ P-gp. Samples from bilaterally and unilaterally pregnant rats were collected throughout gestation, during labor, and PP ( n =4–6/gestational day). RNA and protein were isolated and subjected to quantitative PCR and immunoblotting; P-gp transcript and protein were localized by in situ hybridization and immunohistochemistry. Expression of Abcb1a/1b gene and membrane P-gp protein in uterine tissue (1) increased throughout gestation, peaked at term (GD19-21) and dropped during labor (GD23L); and (2) was upregulated only in gravid but not in empty horn of unilaterally pregnant rats. (3) The drop of Abcb1a/1b mRNA on GD23 was prevented by artificial maintenance of elevated progesterone (P4) levels in late gestation; (4) injection of the P4 receptor antagonist RU486 on GD19 caused a significant decrease in Abcb1 mRNA levels. (5) In situ hybridization and immunohistochemistry indicated that Abcb1/ P-gp is absent from myometrium throughout gestation; (6) was expressed exclusively by uterine microvascular endothelium (at early gestation) and luminal epithelium (at mid and late gestation), but was undetectable during labor. In conclusion, ABC transporter protein P-gp in pregnant uterus is hormonally and mechanically regulated. However, its substrate(s) and precise function in these tissues during pregnancy remains to be determined.